Chromatin conformational changes accompany transcriptional activation of a glucose-repressed gene in Saccharomyces cerevisiae. - Sledziewski, A (1982)
In the present study we have analyzed the kinetics of DNase I digestion of the two alcohol dehydrogenase (ADH) genes within yeast nuclei. We have found that in yeast grown on glucose the constitutively transcribed ADCI gene is much more sensitive to DNase I digestion than is the repressible ADR2 gene. In yeast grown on ethanol, both genes are transcribed and both exhibit the same sensitivity to DNase I attack. We have also found and mapped DNase I hypersensitive sites near the 5' ends of constitutive and repressible ADH genes. These sites are well correlated with the position at which transcription is initiated.